Asymmetric evolutionary game analysis of emergency cooperative social networks for magnitude emergencies: Evidence from the Beijing-Tianjin-Hebei region in China - Nan, Rui; Wang, Jingjie (Frontiers in Physics, 2022)
Emergency cooperative social networks (ECSNs) play a very important role in emergency management for magnitude emergencies in China recently. Based on the data set of cooperative fight against COVID-19 of the Beijing-Tianjin-Hebei region in China, using SNA and asymmetric evolutionary game model, this study finds that the asymmetry between regions is comprehensively determined by resource endowment, administrative level, geographical distance, regional vulnerability, political pressure and other factors; vertical control is still the main operating mechanism of ECSNs; network derivation is caused by the superposition of multiple factors, of which political factors are very important, and asymmetry may become an obstacle.